Motor Command and Supervision Using the Magnetic Components of the Insulation Fault Protection System for Power Line Communication - Matias Fernando Bulacio; Hernan Emilio Tacca (Institute of Advanced Engineering and Science, 2017)
This work proposes an additional function for a VSD (Variable Speed Drive) which sends and receives information over the power lines and simultaneously, implements the protection against insulation faults to earth. Using the magnetic components of the insulation fault protection system of the motor, the prototype injects and detects the communication signals over the power line. The system works on both communication schemes, with and without the PWM (Pulse Width Modulation) perturbation in the power lines, which are the two possible real applications. In order to set a proper communication between the motor and the drive, the communication channel was modeled and the noise was characterized. An FSK modulation and demodulation scheme was developed and tested. A 10 kbps communication over a 125 m length of cable and over a 1 km pi-section model of the same cable was successfully achieved with the laboratory prototype.